2014
DOI: 10.1111/epi.12569
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to replace the Wada test and put awake craniotomy to sleep?

Abstract: SUMMARYThe question we address here is whether the invasive presurgical brain mapping approaches of direct cortical stimulation and of the Wada procedure can be replaced by noninvasive functional neuroimaging methods (functional magnetic resonance imaging [fMRI], magnetoencephalography [MEG], transcranial magnetic stimulation and [TMS]). First, we outline the reasons for contemplating such a replacement. Second, we present evidence to the effect that the efficacy of the invasive and noninvasive methods, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…The observations made in our study are consistent with the previous literature highlighting the utility of non-invasive techniques in identifying eloquent cortex among sedated patients (Papanicolaou et al, 2014). For example, using fMRI Souweidane et al (1999) demonstrated consistent activation in left temporo-parietal and frontal regions in a group of eight children under propofol sedation, in response to passive auditory stimuli consisting of words and sentences, a pattern comparable to that derived in non-sedated subjects using a similar paradigm.…”
Section: Discussionsupporting
confidence: 93%
“…The observations made in our study are consistent with the previous literature highlighting the utility of non-invasive techniques in identifying eloquent cortex among sedated patients (Papanicolaou et al, 2014). For example, using fMRI Souweidane et al (1999) demonstrated consistent activation in left temporo-parietal and frontal regions in a group of eight children under propofol sedation, in response to passive auditory stimuli consisting of words and sentences, a pattern comparable to that derived in non-sedated subjects using a similar paradigm.…”
Section: Discussionsupporting
confidence: 93%
“…The Wada test, or intracarotid amobarbital procedure (IAP), is often used to determine language and memory lateralization in candidates for epilepsy surgery, and has been referred to as the “gold standard” for this purpose. However, with the development of noninvasive functional neuroimaging methods, including functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), and transcranial magnetic stimulation (TMS) to lateralize language function, the continued use of the Wada test has been questioned . One reason is that the Wada test is invasive, as it requires the insertion of a catheter into the internal carotid artery (ICA).…”
mentioning
confidence: 99%
“…However, with the development of noninvasive functional neuroimaging methods, including functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), and transcranial magnetic stimulation (TMS) to lateralize language function, the continued use of the Wada test has been questioned. [1][2][3] One reason is that the Wada test is invasive, as it requires the insertion of a catheter into the internal carotid artery (ICA). The complication rates associated with cerebral angiography and Wada testing range from 0.3% up to nearly 11% of patients undergoing the procedure, with the Wada test reported near the upper end of this range.…”
mentioning
confidence: 99%
“…Based on review of the current literature, Papanicolaou et al . propose that there is sufficient evidence of the superiority of several established functional assessment techniques, and in most cases, it is time “for the Wada procedure to be replaced … and for awake craniotomy to be put to sleep.” Although there is little doubt that the number of cases undergoing Wada testing or cortical stimulation mapping (CSM) has decreased in epilepsy surgery programs in part due to the development and maturation of noninvasive language mapping techniques such as function magnetic resonance imaging (fMRI) and magnetoencephalography (MEG), there are risks in developing broad recommendations asserting that established techniques such as Wada testing and CSM should be abandoned.…”
mentioning
confidence: 99%